A survey on Applicability of bisociation and cognitive learning on Iot based smart watches and SOS Applications - venkateshwara Reddy, H; Arun Kumar, Ravula; Mallikarjun Reddy, G (International Journal of Computer Sciences and Engineering, 2025)
Creativity is the major source that creates the impact on users what the product is and what the content is, the bisociation has the capacity to connect the dissimilar components and the edge of the bisociation we apply the cognitive learning, as the cognitive learning has the byproduct of learning the theme on its own methods that have the capacity of artificial intelligence to maintain the legacy of brining the new ideas and the innovation to the sciences now. The main theme of this survey is based on how the genetic theory with the help of neural network get attached to the study of Iot the watch can sense the information when the person in critical zone and reports the nature and position through GPS. The paper focus mainly on thinking ability and innovation about the types that mature the concept of Iot with smart watch that sense with biological flavor.